2020
DOI: 10.3390/foods9101415
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Peptidases in Intestinal Brush Border Membranes on the Absorption of Oligopeptides from Whey Protein Hydrolysate: An Ex Vivo Study Using an Ussing Chamber

Abstract: For many years, it was believed that only amino acids, dipeptides, and tripeptides could be absorbed and thus reach the bloodstream. Nowadays, the bioavailability of oligopeptides is also considered possible, leading to new research. This pilot study investigates the activity of brush border enzymes on undigested whey protein hydrolysate (WPH) and on simulated intestinal digested (ID) whey hydrolysate and the subsequent absorption of resultant peptides through the proximal jejunum of a 7-week old piglet setup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 53 publications
1
53
0
Order By: Relevance
“…Regarding the correlation of in vitro absorbable product release with in vivo postprandial amino acid responses, it needs to be considered that our in vitro model does not include intestinal brush border enzymes, which have been shown to cleave MMW peptides [ 47 , 48 ]. One approach could therefore be to view TP release in vitro to resemble absorbable product release in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the correlation of in vitro absorbable product release with in vivo postprandial amino acid responses, it needs to be considered that our in vitro model does not include intestinal brush border enzymes, which have been shown to cleave MMW peptides [ 47 , 48 ]. One approach could therefore be to view TP release in vitro to resemble absorbable product release in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Aside the physicochemical characteristics of peptides such as net charge, amino acid sequence and the chain length, hydrophobicity and molecular weight ( Karami & Akbari-adergani, 2019 ), the interaction between AHPs and other components of food matrix used in delivering the peptides, microbiota activities and mucin content of intestinal epithelium have been suggested to influence their biostability, bioavailability, bioaccessibility and biological activities ( Ozorio et al, 2020 ). For example, interactions of certain peptides with micronutrient composition of food matrix such as mineral elements have been demonstrated to influence their bioavailability and permeability ( Sun, Acquah, Aluko, & Udenigwe, 2020 ).…”
Section: Factors That Influence the Antihypertensive Properties And N...mentioning
confidence: 99%
“…Ozorio et al (2020) reported ex vivo studies of piglet small intestinal (jejunum) tissue in the Ussing chamber model. An Ussing chamber is composed of two compartments separated by a tiny sheet of gut mucosa obtained from either biopsy or tissue culture.…”
Section: Can Food Exorphins Stimulate Appetite Through Effects On The...mentioning
confidence: 99%
“…However, the presence of larger peptides in blood under such specific pathophysiological circumstances does not show that gluten exorphins are absorbed under normal physiological conditions, in which the paracellular route is minimal and transport takes place primarily transcellularly, during which the peptides are exposed to cytosolic peptidases that will result in their degradation. Ozorio et al (2020) reported ex vivo studies of piglet small intestinal (jejunum) tissue in the Ussing chamber model. An Ussing chamber is composed of two compartments separated by a tiny sheet of gut mucosa obtained from either biopsy or tissue culture.…”
Section: Are Gut Luminal Exorphins Absorbed To a Significant Extent?mentioning
confidence: 99%